O diretor de escola e a produção de subjetividade : desafios da democratização da escola pública - Almeida, Nathália Suppino Ribeiro de (Universidade Federal de São Carlos, 2016)
The present study had as its object the investigation of discourses present in the perceptions of the school principal about the school democratization and education in Brazil. Therefore, we seek to understand aspects of the production of subjectivity of public school principal among the speeches and democratization processes experienced in our country. They analyzed the statements of public school principals of municipal Ribeirao Preto, with over fifteen years of experience in office, in order to understand how it produces its subjectivity considering the complexity of relationships in which they operate and social, cultural and historical elements that permeate. The methodological bases used guided in qualitative approaches, theoretical and bibliographic interdisciplinary study, semi-structured taped interviews, nonparticipant observation and analysis of speeches in French perspective. The main theoretical framework adopted, based on the theories of Michel Foucault, includes numerous studies on the analysis of speeches and the subject while production of power relations that is part and elements that make up its historical and social context. We note that the speeches concerning the democratic management often define this school management model as one in which the director allows the students at school entry and family that they give opinions freely. However, in many situations, such access is only allowed for matters involving the student in a timely manner, while other matters concerning the institution remain centralized in the head, leaving him, the final decision. The dicurso democratic management by the free access of parents to school, so keep hidden these mechanisms, Aleem to strengthen the authority of the director, the institution away from behaviors that promote democratization.
Keywords: Produção de subjetividade; Diretor de escola; Análise de discursos; Gestão democrática; Production of subjectivity; School principal; Analysis of speeches; Democratic management; CIENCIAS HUMANAS::EDUCACAO